2018
DOI: 10.1292/jvms.17-0319
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil decreases oral tissue blood flow while maintaining internal carotid artery blood flow during sevoflurane anesthesia in rabbits

Abstract: The aim of this study was to investigate the effect of remifentanil infusion on oral tissue blood flow including submandibular gland tissue blood flow (SBF) and internal carotid artery blood flow (ICBF) in rabbits during sevoflurane anesthesia. Twelve male Japan White rabbits were anesthetized with sevoflurane and remifentanil. Remifentanil was infused at 0.2 and 0.4 µg/kg/min. Measurements included circulatory variables, common and external carotid artery blood flow (CCBF, ECBF), ICBF, tongue mucosal blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Remifentanil has been interacted with the α2-adrenoreceptor and might constrict peripheral vasoconstriction in the masseter muscle and mandibular bone marrow [8,11,14]. Hirata et al reported that calculated peripheral vascular resistance in the masseter muscle and mandibular bone marrow increased during remifentanil infusion [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Remifentanil has been interacted with the α2-adrenoreceptor and might constrict peripheral vasoconstriction in the masseter muscle and mandibular bone marrow [8,11,14]. Hirata et al reported that calculated peripheral vascular resistance in the masseter muscle and mandibular bone marrow increased during remifentanil infusion [10].…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil has been interacted with the α2-adrenoreceptor and might constrict peripheral vasoconstriction in the masseter muscle and mandibular bone marrow [ 8 , 11 , 14 ]. Hirata et al reported that calculated peripheral vascular resistance in the masseter muscle and mandibular bone marrow increased during remifentanil infusion [ 10 ]. Therefore, it is considered that the peripheral vascular resistance of the masseter muscle and the mandibular bone marrow might increase and the tissue blood flow decreased during remifentanil infusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations